2017
DOI: 10.1007/s12011-017-1060-9
|View full text |Cite
|
Sign up to set email alerts
|

Effect of High Dietary Manganese on the Immune Responses of Broilers Following Oral Salmonella typhimurium Inoculation

Abstract: Manganese (Mn) is an essential nutrient for both host and pathogen. Recent studies have demonstrated the nutritional immunity of Mn against Salmonella infection in mammals. To investigate the effect of high dietary Mn on immune responses of broilers following Salmonella challenge, 144 1-day-old male broilers were fed a basal diet (containing 20.04 mg Mn/kg) plus an additional 40 (the control group) or 400 mg Mn/kg (the H-Mn group) for 7 days. The 72 broilers in each group were then orally inoculated with 5 × 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 49 publications
2
27
0
Order By: Relevance
“…On day 7, broilers were orally inoculated with either 0 or 0.5 × 10 8 CFU Salmonella enterica serovar Typhimurium (ST), according to the previous assignment (non-challenged vs. challenged). The method is detailed elsewhere [22]. The strain of ST used in this experiment was from the American Type Culture Collection (ATCC, No.…”
Section: Oral Salmonella Inoculationmentioning
confidence: 99%
See 1 more Smart Citation
“…On day 7, broilers were orally inoculated with either 0 or 0.5 × 10 8 CFU Salmonella enterica serovar Typhimurium (ST), according to the previous assignment (non-challenged vs. challenged). The method is detailed elsewhere [22]. The strain of ST used in this experiment was from the American Type Culture Collection (ATCC, No.…”
Section: Oral Salmonella Inoculationmentioning
confidence: 99%
“…2), which is considered to be a response by the host defence system. A great deal of literature has already revealed that immune organs play crucial roles in the defence against Salmonella [22]. Whether the host will alter the zinc metabolism of their immune organs in response to Salmonella challenge remains unknown until now.…”
Section: Zinc Was Also Redistributed Into the Bursa Of Fabriciusmentioning
confidence: 99%
“…Meanwhile, inflammatory cytokines such as interleukin (IL)-1, IL-6, IL-17, and IL-22, together with interferon-γ (IFN-γ) are released after infection, either by epithelial cells, resident phagocytes, infiltrating phagocytes, and/or lymphocytes in the cecum [3,10,11]. Recent data from our laboratory demonstrates that a similar cytokine gene expression pattern can be recorded in spleen, thymus, and bursa of broilers [12]. Oral S. Typhimurium challenge also was found to change the cluster of differentiation 4 (CD 4+ ) and CD 8+ cells ratios and increase the gene expression of IL-1β, IL-8, IFN-γ, and IL-18 in the spleens of hens, similar to the response in the cecum after oral infection with Salmonella [13].…”
Section: Introductionmentioning
confidence: 99%
“…It is also an essential trace element of normal metabolism in humans and animals. The roles that Mn plays in innate and adaptive immune responses are well established in broilers [12], rats [16], and humans [17]. For instance, adding Mn to a diet could increase the phagocytic ability of natural killer cells of rats [16].…”
Section: Introductionmentioning
confidence: 99%
“…However, there is evidence that high levels of manganese may impair immune function. Experimental studies in rodents and birds have shown that manganese exposure can cause a significant changes in lymphocyte responses and reduced antibody production [14], as well as increased susceptibility to bacterial and viral infection [15,16]. Although epidemiologic evidence of manganese-related immunological effects is primarily restricted to occupational studies of adult men, high occupational exposure has been associated with significantly altered lymphocyte profiles (e.g.…”
Section: Introductionmentioning
confidence: 99%